Social life cycle assessment (SLCA) for palm oil production in Malaysia - Muhammad, Khairul Izzuddin; Muhamad Pauzi, Muhamad Faiz; Sharaai, Amir Hamzah (American-Eurasian Network for Scientific Information (AENSI) Publications, 2015)
Background: The study of Social Life Cycle Assessment (SLCA) is one of many researches that provide an overall view of potential social impacts, which are identified from the whole life cycle of the product. This SLCA study focuses on the processing of crude oil from the whole life cycle of palm oil products at Gua Musang, Kelantan, Malaysia. This research involves two stakeholders i.e. workers and the local community. Objective: The purpose of this research is to identify potential social impacts (midpoint impacts from workers and the local community) throughout the whole life cycle of palm oil production using the SLCA methodology. Results: The results reveal that, in regards to the social aspect, workers experience a high level of job satisfaction. For the local community, the satisfaction levels are different according to specific categories especially for those that do not have any major impact on the local community. In short, social significance remains a top priority and these workers and the local communities must give due attention to this issue. Conclusion: The overall social aspects derived from the SLCA for palm oil production has met the required criteria in terms of social significance for those who are in direct contact with this operation.